Labetalol Versus Nifedipine as Antihypertensive Treatment for Chronic Hypertension in Pregnancy: A Randomized Controlled Trial. Issue 5 (November 2017) - Webster, Louise M.; Myers, Jenny E.; Nelson-Piercy, Catherine; Harding, Kate; Cruickshank, J. Kennedy; Watt-Coote, Ingrid; Khalil, Asma; Wiesender, Cornelia; Seed, Paul T.; Chappell, Lucy C.
Abstract : Data from randomized controlled trials to guide antihypertensive agent choice for chronic hypertension in pregnancy are limited; this study aimed to compare labetalol and nifedipine, additionally assessing the impact of ethnicity on treatment efficacy. Pregnant women with chronic hypertension (12 +0 –27 +6 weeks' gestation) were enrolled at 4 UK centers (August 2014 to October 2015). Open-label first-line antihypertensive treatment was randomly assigned: labetalol- (200–1800 mg/d) or nifedipine-modified release (20–80 mg/d). Analysis included 112 women (98%) who completed the study (labetalol n=55, nifedipine n=57). Maximum blood pressure after randomization was 161/101 mm Hg with labetalol versus 163/105 mm Hg with nifedipine (mean difference systolic: 1.2 mm Hg [−4.9 to 7.2 mm Hg], diastolic: 3.3 mm Hg [−0.6 to 7.3 mm Hg]). Mean blood pressure was 134/84 mm Hg with labetalol and 134/85 mm Hg with nifedipine (mean difference systolic: 0.3 mm Hg [−2.8 to 3.4 mm Hg], and diastolic: −1.9 mm Hg [−4.1 to 0.3 mm Hg]). Nifedipine use was associated with a 7.4-mm Hg reduction (−14.4 to −0.4 mm Hg) in central aortic pressure, measured by pulse wave analysis. No difference in treatment effect was observed in black women (n=63), but a mean 4 mm Hg reduction (−6.6 to −0.8 mm Hg; P =0.015) in brachial diastolic blood pressure was observed with labetalol compared with nifedipine in non-black women (n=49). Labetalol and nifedipine control mean blood pressure to target in pregnant women with chronic hypertension. This study provides support for a larger definitive trial scrutinizing the benefits and side effects of first-line antihypertensive treatment. Clinical Trial Registration—: URL:https://www.isrctn.com . Unique identifier: ISRCTN40973936. Abstract : Supplemental Digital Content is available in the text.